Kajian Penyebab Kemarahan Menurut Suttapiṭaka dalam Masyarakat Multikultural: Perspektif Psikologi Sosial - Julia Surya (Mahesa Research Center, 2021)
The research aims at investigating the causes of anger from the perspective of Buddhist sociology as explained in the Sutta Pittaka and Social Psychology. It was a qualitative research employing hermeneutics approach. The data analysis included (1) deciding the texts to be examined, (2) reading and understanding the texts, (3) describing and interpreting, and (4) drawing conclusion towards the meanings of the texts. The results showed that generally, the causes of anger according to Sutta Pittaka were explained in Ayonisomanasikāra Sutta, Saṁyutta Nikāya, Majjhima Nikaya, Saṁyutta Nikaya, and Aṅguttara Nikāya. The suttas explained that anger happened because of the contact (phassa) towards eyes (cakkhu) and form (rūpa), and eyes consciousness (cakkhu-viññāṇa). Sociologically, based on the individual and social aspect, Suttapiṭaka mentioned that the causes of anger were from the economic, ideology, and unethical deeds aspects. Social Physchology mentioned that angers were caused by internal and external things. Therefore, the causes of anger in the view of Suttapiṭaka, from sociological views and Social Physchology rooted from individual’s feeling and response towards what other did to him/her.